2023
DOI: 10.1159/000529670
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in Ventricular Arrhythmias

Abstract: Background Ventricular ectopy is observed in most of the population ranging from isolated premature ventricular contractions to rapid hemodynamically unstable ventricular tachyarrhythmias like ventricular tachycardia and ventricular fibrillation. Multiple mechanisms exist for ventricular arrhythmias such as triggered activity, reentry, and automaticity. Scar-based reentry forms the basis of most malignant VA that can lead to sudden cardiac death. Many antiarrhythmic drugs have been utilized for the suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The Cardiac Arrhythmia Suppression Trial (CAST) as well as subsequent studies showed that, while these drugs reduce the incidence of arrhythmias significantly, they may lead to a 3.6-fold increased risk of sudden cardiac death. This perceived pro-arrhythmogenic effect led to an overall decline in their utilization and are now restricted to a limited range of indications (1)(2)(3). In contrast, ablation therapy has grown increasingly popular for the management of various arrhythmias, including atrial fibrillation (AF) and ventricular tachycardia (VT).…”
Section: Introductionmentioning
confidence: 99%
“…The Cardiac Arrhythmia Suppression Trial (CAST) as well as subsequent studies showed that, while these drugs reduce the incidence of arrhythmias significantly, they may lead to a 3.6-fold increased risk of sudden cardiac death. This perceived pro-arrhythmogenic effect led to an overall decline in their utilization and are now restricted to a limited range of indications (1)(2)(3). In contrast, ablation therapy has grown increasingly popular for the management of various arrhythmias, including atrial fibrillation (AF) and ventricular tachycardia (VT).…”
Section: Introductionmentioning
confidence: 99%